Reported Speech in Medical Activity - Vieira, Marcos A. M. (The ESPecialist, 2012)
Viewing medical work in the perspective of language as an activity, we studied the dialogue difficulties between infectologists and AIDS patients. Our objective was to describe the discursive uses that enable the effective rendering of this practice. Supported by Bakhtin’s notions of dialogism and discourse genres, we used reported speech as our instrument of analysis. The direct speech describes the activity, the indirect speech argues and negotiates a discursive “consensus”, and the citation hybrids enable a renormalization of the activity in the discursive field. The results indicate the readjustment of a work practice in the empirical field and point to the construction of a discursive genre of the activity.